Awareness and practice of dentists in gulf cooperation council countries regarding medication-related osteonecrosis of the jaw – A web-based survey - Mohammad Zakaria, Nassani (2023)
Background/purposeMedication-related osteonecrosis of the jaw (MRONJ) is a serious complication among dental patients undergoing treatment with antiresorptive medications such as bisphosphonate and denosumab. The present survey investigated the awareness and practice of dentists in the Gulf Cooperation Council (GCC) countries regarding MRONJ. Materials and methodsThis questionnaire-based study was conducted among dental practitioners in all six GCC countries. A questionnaire was designed and distributed among all potential participants via different social media platforms. SPSS version 22 was used for data analysis, and P-value <0.05 was considered statistically significant. ResultsOverall, 1685 dentists from the six GCC countries participated in the present study. The surveyed dentists revealed relatively fair practices and awareness regarding MRONJ and its prevention, with the majority reported asking their patients about history of anti-osteoporotic medications (67.8%), recording name of the medication (73.1%) and duration of treatment (75.5%). However, the majority of the participants were unconfident about the duration of drug holiday prior to dental surgical interventions (70.6%) and the overall good level of knowledge/practice related to MRONJ was just 50.6%. The regression analysis revealed that previous exposure to MRONJ cases and attending a seminar, course, meeting, or conference about osteonecrosis of the jaw were independent predictors for positive awareness/good practice regarding MRONJ (P < 0.05). ConclusionThe results show inadequate awareness and practices of dentists practicing in GCC countries regarding MRONJ, with significant variations among the countries. Therefore, appropriate interventions such as periodic continuous education courses are required to improve dentists’ knowledge and practices regarding MRONJ.